The effect of oxytocin and cloprostenol application via umbilical artery immediately after dystocia on time and rate of fetal membrane removal in cows - Akar, Yasar; Kizil, Omer; Saat, Nevzat; Yuksel, Murat (Tubitak Scientific & Technological Research Council Turkey, 2012)
The aim of this clinical study was to investigate the effects of oxytocin and cloprostenol application via umbilical artery on the time and rate of fetal membrane removal in cows with dystocia immediately aft er parturition. Metabolic profiles indicated certain serum biochemical parameters that were also determined in the cows. The study was performed on 60 cows with dystocia. All of the cows were randomly divided into 3 equal subgroups. The first group was injected with 100 IU oxytocin, while the second group was treated with 0.15 mg cloprostenol and the third group (the control group) received 10 mL 0.9% NaCl via intraumbilical artery. Blood samples were randomly taken from the jugular veins of 10 cows from each group. No significant differences were determined between the groups with regard to the values of aspartate aminotransferase, alkaline phosphatase, creatine kinase, total protein and bilirubin, albumin, glucose, Ca, Na, or K (P > 0.05). The lactate dehydrogenase level in the oxytocin group was determined to be significantly lower when compared to the cloprostenol and control groups (P < 0.05). The value of gamma-glutamyl transferase in the oxytocin group was significantly higher than in the other groups (P < 0.05). The time and rate of fetal membrane removal were not different among the groups (P > 0.05). In conclusion, the administration of combinations of other uterotonics and enzymes together with these agents should be investigated to determine the effects on cows with retained placenta prophylaxis. Future applications may also study the effects of these agents on fertility and time and rate of fetal membrane removal in cows with normal parturition and dystocia at the herd level.
Keywords: Cloprostenol; cow; dystocia; fetal membrane; oxytocin; umbilical cord